A Natural History of Oregon's Lake Abert in the Northwest Great Basin Landscape - Larson, Ronald J. (Book collections on Project MUSE., 2023)
"A Natural History of Oregon's Lake Abert in the Northwest Great Basin Landscape focuses on the salt lake and includes descriptions and numerous photos of the region's geology, hydrology, and plants and animals-from lichens to pronghorn sheep-as well as its archaeology. Because birds are so conspicuous, both on the lake and in the uplands, there is an abundant amount of information included about them"--